Analisis Peningkatan Remineralisasi Enamel Gigi setelah Direndam dalam Susu Kedelai Murni (Glycine max (L.) Merill) Menggunakan Scanning Electron Microscope (SEM) (The Analysis of Enamel Remineralization Increase in Pure Soy Milk (Glycine max (L.) Merill) - Vievien - Widyaningtyas; Yani Corvianindya Rahayu; Izzata - Barid (UPT Percetakan dan Penerbitan Universitas Jember, 2014)
Pure soy milk has a high mineral content, they are calcium and phosphor. Both minerals are important mineral in enamel remineralization process. Remineralization is the return process of mineral teeth that has detached to back return be hidroxyapatite cristal enamel. This research was aimed to analyze the enamel remineralization increase after being immersed in pure soy milk (Glycine max (L.) Merill). The type of this research is experimental laboratories with the post test control group design. The sampel of this research was first maxillary premolar which caries-free. The sample was divided into two groups (control and pure soy milk treatment) and each group had four samples. The sample immersion was incubated in 14 days by incubator in 37°C, control group was immersed in artificial saliva and the treatment group was immersed in pure soy milk. The analysis of enamel remineralization used Scanning Electron Microscope with remineralization indicator was the depth of enamel microporocity. The result of this research showed that the enamel tooth samples that was immersed in pure soy milk had less microporocity depth than the sample that was immersed in artificial saliva, with significance level 0.000 (p<0.005). The conclusion of this research was pure soy milk can increase enamel remineralization. Keywords: calcium, enamel microporocity, phosphor, pure soy milk, remineralization, SEM